The case for increasing diversity in tissue-based functional genomics datasets to understand human disease susceptibility - Erping Long; Montserrat García-Closas; Stephen J. Chanock; M. Constanza Camargo; Nicholas E. Banovich; Jiyeon Choi (Nature Communications, 2022)
Tissue-based functional genomics resources including molecular quantitative trait loci datasets lack diversity in ancestry and tissue types and thus are inadequate for comprehensively investigating gene regulation. Global efforts to increase the tissue diversity will help achieve more equitable medical care.